THE EFFECT OF COLLABORATIVE WRITING STRATEGY ON STUDENTS' ACHIEVEMENT IN WRITING RECOUNT TEXT - Nur, Serliah; Tsuraya, Annisa Shofa; Amin, Nurul Latifa (English Language, Linguistics, and Culture International Journal, 2023)
This study aims to determine the effect of implementing collaborative writing strategies on student achievement in writing with the main objective: to determine whether there is a significant effect of collaborative writing strategies on student achievement in writing recount texts. This research was conducted using a quasi-experimental research design. The population of this research is grade ten of one of the senior high school students. Two classes were taken as samples of this study. The experimental group was taught using the Collaborative Writing strategy, while the controlled group was taught using the conventional method. The data collection instrument was a written test. The results showed that the use of Collaborative Writing strategies increased students' achievement in writing recount texts. Evidenced by a significant 2-tailed level for the t-test, namely 0.005 <0.05, which means H1 is accepted and H0 is rejected. This means that there is a significant effect of using Collaborative Writing strategies on student achievement in writing recount texts. Therefore, it is suggested that English teachers apply a collaborative writing strategy to students' learning achievement in writing. Based on the observation of teaching experience it is said that students are more enthusiastic to participate in learning. They have the motivation to write. They are also able to create positive relationships when they work collaboratively in groups. That's because they have many pairs of eyes for writing correction. In addition, students are allowed to give and received direct feedback on the language used in their writing. Thus, the teaching-learning process becomes more interesting and students enjoy a better writing process in recount texts.